Aberrant spinal mechanical loading stress triggers intervertebral disc degeneration by inducing pyroptosis and nerve ingrowth - Fangda Fu (Nature Portfolio, 2021)
Abstract Aberrant mechanical factor is one of the etiologies of the intervertebral disc (IVD) degeneration (IVDD). However, the exact molecular mechanism of spinal mechanical loading stress-induced IVDD has yet to be elucidated due to a lack of an ideal and stable IVDD animal model. The present study aimed to establish a stable IVDD mouse model and evaluated the effect of aberrant spinal mechanical loading on the pathogenesis of IVDD. Eight-week-old male mice were treated with lumbar spine instability (LSI) surgery to induce IVDD. The progression of IVDD was evaluated by μCT and Safranin O/Fast green staining analysis. The metabolism of extracellular matrix, ingrowth of sensory nerves, pyroptosis in IVDs tissues were determined by immunohistological or real-time PCR analysis. The apoptosis of IVD cells was tested by TUNEL assay. IVDD modeling was successfully produced by LSI surgery, with substantial reductions in IVD height, BS/TV, Tb.N. and lower IVD score. LSI administration led to the histologic change of disc degeneration, disruption of the matrix metabolism, promotion of apoptosis of IVD cells and invasion of sensory nerves into annulus fibrosus, as well as induction of pyroptosis. Moreover, LSI surgery activated Wnt signaling in IVD tissues. Mechanical instability caused by LSI surgery accelerates the disc matrix degradation, nerve invasion, pyroptosis, and eventually lead to IVDD, which provided an alternative mouse IVDD model.